A framework for the resilience analysis of complex natural gas pipeline networks from a cyber-physical system perspective. (December 2021) - Marino, Antonio; Zio, Enrico
Highlights: Gas pipeline transmission networks show a high interdependence with SCADA systems. The resilience of complex systems must be studied in an integrated way. Gas pipeline networks may be vulnerable to cyber and physical scenarios. DDoS attacks could demage pipelines causing explosions. Abstract: The vulnerability of gas pipeline networks to physical and cyber-attacks calls for a resilience analysis based on models, capable of quantifying the network robustness and recovery from failures. This work proposes an original resilience analysis framework for a complex gas pipeline transmission network, considering the cybernetic interdependence of the physical gas pipeline network with the SCADA system. The maximum flow algorithm computes the gas network supply capacity and when a failure occurs, the pressure of the network nodes and the gas supply capacity change, leading to dissatisfaction of customer demands. The framework allows quantifing the value of resilience through specific performance metrics. The SCADA communication network, implemented in Network Simulator®, provides the necessary information regarding the delay of data packets coming from the sensors located along the pipelines. The packet delay value allows to evaluate the actual time at which the SCADA system blocks the remote control valves, ready to keep the pipelines under pressure when a failure occurs. Important insights on the resilience model are obtained through a systematic sensitivity analysis (SA) framework, customized for gas pipeline transmission networks. Specifically, we investigate the influence of model inputs to the network robustness and recovery uncertainty. The effects of individual parameters and groups formed by inputs with similar functionalities provide useful information, such as to what extent the supervisory SCADA system interconnection affects the degradation and the recovery process of the physical gas pipeline network. The results of the case study confirm, as expected, that gas transmission networks are vulnerable to both cyber and physical failures, pointing at the need for systemic methods of analysis for managing the system resilience.